Bóg objawiający się w przyrodzie według Psalmów - Niedźwiedzki, Tomasz (Verbum Vitae, 2017)
The experience of divine revelation, which took place throughout the history of the chosen nation, is of the utmost importance in the Hebrew Bible and, consequently, also in the pursuit of biblical exegesis. One should not forget, however, that God reveals himself through natural phenomena as well, an idea which is frequently underscored in the psalter. The present article analyses those psalms which especially describe the Creator’s activity of self-revelation through nature, and point toward the possibility of discovering his divine attributes in man’s contemplation of it. The very fact that God created the universe and everything that exists in it leads one to assume that he also impressed on it some of his attributes, just as artisans or artists leave their mark on the objects they fashion. According to the psalmist, nature is neither passive nor dumb, but is actively involved in praising the Lord, cooperates with him in saving human beings, and always reflects in some way his divine attributes.